Anti-inflammatory effect of luteoloside against methylglyoxal induced human dental pulp cells - Ji-Eun, Kim; Paras Man, Pradhan; Jang, Sungil; Yi, Ho-Keun (Journal of applied biomedicine, 2024)
PURPOSE: The aim of this study was to investigate whether luteoloside, a flavonoid, could protect human dental pulp cells (HDPCs) against inflammation and oxidative stress induced by methylglyoxal (MGO), one of the advanced glycated end products (AGE) substances. METHODS: HDPCs were stimulated with MGO and treated with luteoloside. MTT assay was used to determine cell viability. Protein expression was measured via western blotting. Reactive oxygen species (ROS) were measured with a Muse Cell Analyzer. Alkaline phosphatase activity (ALP) and Alizarin red staining were used for mineralization assay. RESULTS: Luteoloside down-regulated the expression of inflammatory molecules such as ICAM-1, VCAM-1, TNF-α, IL-1β, MMP-2, MMP-9, and COX-2 in MGO-induced HDPCs without showing any cytotoxicity. It attenuated ROS formation and enhanced osteogenic differentiation such as ALP activity and Alizarin red staining in MGO-induced HDPCs. Overall, luteoloside showed protective actions against inflammation and oxidative stress in HDPCs induced by MGO through its anti-inflammatory, anti-oxidative, and osteogenic activities by down-regulating p-JNK in the MAPK pathway. CONCLUSION: These results suggest that luteoloside might be a potential adjunctive therapeutic agent for treating pulpal pathological conditions in patients with diabetes mellitus.
Keywords: luteolin; Luteolin; zubní dřeň; Inflammation; osteogeneze; reaktivní formy kyslíku; Dental Pulp; Glucosides; zánět; Reactive Oxygen Species; kultivované buňky; Anthraquinones; lidé; Humans; pyruvaldehyd; Pyruvaldehyde; anthrachinony; Cells, Cultured; antiflogistika; Osteogenesis; Anti-Inflammatory Agents; glukosidy; oxid hořečnatý; Magnesium Oxide